An Overview of Nursing Diagnosis in Patients with Heart Failure in the Emergency Department - Hidayati, Nur; Hanafi, Aprelia Afidatul; Lailah, Kumil; Othman, Hamidah (Universitas Negeri Gorontalo, 2025)
Heart failure is a leading global cause of mortality. Accurate diagnosis is crucial as the basis for appropriate nursing care. This study aims to identify nursing diagnoses observed in heart failure patients treated at the Emergency Department of Lamongan Muhammadiyah Hospital. A retrospective descriptive-analytic design was applied to 284 medical records of heart failure patients such as admitted between January and December 2023 from 986 patients totally, selected through cluster random sampling. The Study conducted in February 2024. Data were collected via recapitulation and analyzed using frequency distribution. Results indicate symptoms of heart failure including shortness of breath, increased respiratory rate, tachycardia, arrhythmias on ECG, nasal flaring, edema, hypertension, pain, anxiety, altered PCO2 levels, use of accessory muscles for breathing, reduced PO2, fatigue, hypotension, dyspnea, pale skin, CRT >3 seconds, cold extremities, and decreased consciousness. The most common nursing diagnoses included ineffective breathing patterns, acute pain, decreased cardiac output, activity intolerance, ineffective airway clearance, and hypervolemia. The nursing diagnoses obtained in this study have different priorities with the theory because some patients have various condition in the first day admitted in the hospital. Further research is needed with a realtime data and compared with complicated heart failure.